Crossing the line women's interracial activism in South Carolina during and after World War II - Jones-Branch, Cherisse (Univ. Press of Florida, 2014)
The author explores how South Carolina women reacted to the mid-century social and political climate to challenge the racial status quo in their state. She focuses on the interaction of black and white women in a variety of organizations and explores the limitations of interracial activism